1997
DOI: 10.1099/0022-1317-78-1-131
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity in vivo and encapsidation of recombinant human immunodeficiency virus type 1 proteinase expressed in baculovirus-infected cells.

Abstract: The activity in vivo of HIV-1 proteinase (PR) was analysed in the baculovirus expression system, using eight different constructs of the prt gene under the control of polyhedrin (PH) promoters of various strengths. None of the active PRs was expressed in substantial quantities, and only PHfused and/or non-functional PR mutants accumulated in high amounts in insect cells. However, enough PR activity was generated from a lengthened PR construct in insect cells to process Gag polyprotein substrate co-expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 39 publications
(32 reference statements)
3
30
0
Order By: Relevance
“…Using a baculovirus expression system, Royer et al (1997) created recombinant HIV-1 Gag-Pol constructs containing various lengths of PR-inactivated Pol sequence fused inframe to the C-terminal p6 of Pr55gag; they reported that the constructs were barely detectable in culture supernatants. They also reported that the p6-containing Gag-Pol constructs were capable of trans-dominantly inhibiting Gag particle release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a baculovirus expression system, Royer et al (1997) created recombinant HIV-1 Gag-Pol constructs containing various lengths of PR-inactivated Pol sequence fused inframe to the C-terminal p6 of Pr55gag; they reported that the constructs were barely detectable in culture supernatants. They also reported that the p6-containing Gag-Pol constructs were capable of trans-dominantly inhibiting Gag particle release.…”
Section: Discussionmentioning
confidence: 99%
“…may counteract the promoting effect of p6gag on GagPR release. However, in a separate study using an insect cell system, p6gag within PR-inactivated Gag-Pol (similar to the Gag(p6)Pol construct) was observed as markedly reducing VLP yields, as well as quantities of VLP-associated Gag-Pol (Royer et al, 1997). Royer et al therefore suggest that p6gag within Gag-Pol exerts a negative impact on VLP production in addition to impeding Gag(p6)Pol viral incorporation.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, virus load assays based on genome copy number determination explore the genome encapsidation process and not specifically the capsid assembly, although RNA encapsidation and virus assembly have been shown to be two linked phenomena [56][59]. Several laboratories, including ours, have fused an enzyme to the Gag precursor, e.g bacterial beta-galactosidase [31], [60] or firefly luciferase [22], to quantitate VLP in cell culture supernatants using enzymatic assays. Other methods have preconized the fusion of Gag to enhanced green fluorescent protein from jellyfish Aequorea (eGFP), to be able to monitor Gag assembly and budding by flow cytometry, or by fluorescence microscopy in situ in cell compartments [61], [62].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, retroviral PR domains are extremely insoluble (6,10,21). Expression of an HIV-1 Gag protein with an inactivated PR domain at its C terminus (creating a molecule equivalent to RSV Gag) resulted in a reduction of extracellular VLP production by 5-to 10-fold compared with wild-type Gag, and the particles produced had a lower density and were irregular in shape (19). These data suggest that the PR domain might lead to unnatural aggregation or precipitation of RSV Gag in the baculovirus overexpression system, in effect preventing proper budding.…”
mentioning
confidence: 99%